Ramadan Munggahan tradition in West Java: Celebrating Culture and Religious Values - Rizal, Saeful; Gibar, Faizal Azzriel; Nugraha, Akbar Wira; Buccharelli, M Riza; Nurjaman, Asep Rudi; Jenuri, Jenuri (Indonesian Culture and Religion Issues, 2024)
The purpose of this research is to discuss Islamic values, especially in the Sundanese tribe in West Java, from a tradition Munggahan. The Munggahan tradition is an event that is always celebrated by Muslims before welcoming the holy month of Ramadan. The research method is qualitative with field studies using descriptive methods to analyze complex and clear data. The research discusses the definition of Munggahan, munggahan tradition according to Islam, traditional activities carried out, and Islamic values contained in munggahan. The conclusion of the research is that Munggahan is a hereditary cultural heritage carried out by the Sundanese community and is a tradition that needs to be preserved by us as citizens of West Java. In Islamic law, there is no prohibition for the implementation of the Munggahan tradition, if all is done without any elements of misguidance and aims to establish friendship among Muslims, especially in West Java. Munggahan tradition has so much meaning and wisdom without any specific prohibition in the Qur'an that regulates this tradition. This research is expected to contribute in maintaining the Islamic values and culture of the Munggahan tradition for efforts to preserve culture in Indonesia.